Pumping up adoption: The role of policy awareness in explaining willingness to adopt heat pumps in Canada. (February 2023) - Corbett, Meghan; Rhodes, Ekaterina; Pardy, Aaron; Long, Zoe
Abstract: Heat pumps are a key technology for decarbonising residential buildings, yet their current market share in Canada remains very low at approximately 5 %. To promote heat pump adoption, governments in Canada have introduced supportive policies such as purchase subsidies, and it is often assumed that increasing consumer awareness of such policies increases heat pump adoption. Using a survey of Canadian homeowners who do not own heat pumps ( n  = 3138), we assess: (1) levels of willingness to adopt air source and ground source heat pumps across Canada, (2) the effect of information provision on willingness to adopt heat pumps, (3) levels of heat pump policy awareness across Canada, (4) whether perceived technical characteristics of heat pumps can be categorized as functional or symbolic, and as private or societal, and (5) the role of policy awareness and other drivers in explaining willingness to adopt heat pumps. We find that a third of Canadian homeowners express willingness to adopt heat pumps. These homeowners are found predominantly within the Atlantic region and show higher levels of adoption willingness for air source rather than ground source heat pumps. Awareness of existing heat pump supportive policy is low, with only 5 % of respondents able to name any policies from memory. Awareness tends to be higher in British Columbia, and for heat pump subsidies and carbon taxes. Policy awareness without cues (i.e., being able to freely recall policies) is a positive predictor of willingness to adopt air source heat pumps only. Policy awareness with cues (i.e., when respondents were provided with a list of policies that served as a memory prompt) is not associated with willingness to adopt either type of heat pump. Other significant predictors include perceptions of heat pumps' functionality and their environmental benefits, having a technology-oriented lifestyle, having higher support for policies, and the financial and inconvenience costs during installation. Based on findings, insights into targeted policy designs to accelerate residential building decarbonisation are provided. Highlights: A third of Canadian homeowners are willing to adopt a heat pump. Awareness of heat pump supportive policy is generally low. Policy awareness is associated with the adoption of air source heat pumps. Providing technical information is not associated with higher heat pump adoption. Other characteristics are associated with heat pump adoption.